INTEGRATED REHABILITATION PROGRAM FOR PERSONNEL WITH DISABILITIES IN THE MINISTRY OF DEFENSE AND INDONESIAN NATIONAL ARMED FORCES - Ari Wijayanti; Puput Oktaminanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: In carrying out their main duties, soldiers are often confronted with risks that can cause them to have disabilities either when carrying out operational tasks or having accident in the service. Efforts to improve the life of persons with disabilities are empowered through integrated rehabilitation process for Personnel of The Ministry of Defense of the Republic of Indonesia and Indonesian National Armed Forces with disabilities. This research was aimed to describe and analyzing the integrated rehabilitation on persons with disabilities at the Ministry of Defense Rehabilitation Center, and describing the factors that support and inhibit the implementation of integrated rehabilitation. Methods: This research was a descriptive qualitative research with an in-depth interview as instrument to obtain data from informants who were the participants of integrated rehabilitation.With Triangulation the source was the instructor and the rehabilitation organizer. Results: Based on the results of interview analysis conducted, the researchers also have identified several supporting factors and inhibiting factors on the implementation of integrated rehabilitation program. The inhibiting factors are Resources: the limited number of instructors (human resources) that have sufficient competence and the lack of facilities for the accessibility of persons with disabilities this will hinder the implementation of rehabilitation. From the results of research indicates that communication, disposition and bureaucratic structure is a supporting factor in the implementation of integrated rehabilitation. Conclusions: Implementation of integrated rehabilitation has been running well although there are still inhibiting factors. Therefore, the Ministry of Defense Rehabilitation Center should continue to strive to become professional rehabilitator in order to create self-sufficient and productive persons with disabilities so as to improve their welfare.